Analisa Dampak Distributed Generation (DG) Dalam Perhitungan Drop Tegangan Pada Jaringan Distribusi - Muhammad Septian Dwi Cahyo; Azriyenni Azhari Zakri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The power plant is a long way from the center of the load, and this results in considerable power losses and electrical voltage on the distribution of electrical power. This loss is caused by a long electrical transmission line and the type of conductor used. In the distribution of electrical energy through transmission and distribution, a voltage drop will take place throughout the line. This study will evaluate the magnitude of the voltage drop that occurs at the Jendral Sudirman feeder in Pekanbaru, Riau. There are several methods that can be made to improve the voltage drop. So this study will use the Distributed Generation (DG) installation method in the distribution network. In the initial data collection, the voltage drop on the feeder was 18.657 kV, equivalent to 6.72%. The voltage drop value exceeded the PLN standard, which was 5% of the nominal voltage. To improve the voltage drop in DG pair on the distribution network on the general Sudirman road feeder of 19.893 kV. Finally, from the analysis obtained the value of the voltage drop becomes reduced from before the installation of DG with the DG installed. The value of the voltage drop produced is far better at 0.53%, and this value has met the standard PLN that has been set.Keywords: Distributed Generation, Power Flow, Voltage Drop